Ship stability for masters and mates - Barrass, C. B. (Elsevier / BH, 2012)
Understanding ship stability - the ability of a ship to return to an initial state after disturbing forces and moments - is critical for all maritime students and professionals studying for a deck or engineering certificate of competency, or seeking promotion to a higher rank within marine or naval companies or institutions. The seventh edition of this classic text provides a comprehensive introduction to all aspects of ship stability and ship strength, squat, interaction and trim, materials stresses and forces, with numerous worked examples to assist masters, mates and engineering office.